ANALISIS PENEGAKAN HUKUM TINDAK PIDANA PENCUCIAN UANG TANPA PUTUSAN PIDANA ASAL KORUPSI - Johri; Rodliyah; Rina Rohayu Harun (The Juris, 2023)
This research aims to analyze the process of law enforcement and prevention of money laundering crimes originating from corruption based on Law Number 8 of 2010 on the Prevention and Eradication of Money Laundering Crimes and the efforts made by third parties acting in good faith to recover their assets if the money laundering crime is not proven in the corruption offense. The research method used in this study is a normative legal research method. From the analysis conducted, the legal enforcement mechanism for money laundering crimes originating from corruption as the underlying offense is essentially bound by the Criminal Procedure Code (KUHAP), the Money Laundering Act, and the Corruption Criminal Act. In the law enforcement process for money laundering crimes, there are still obstacles, both in terms of substantive law (substantive law) and procedural law (formal law). Additionally, the efforts that can be made by third parties to recover their assets are not sufficiently regulated in Law Number 8 of 2010, which means that it may not fully satisfy the principles of justice and legal certainty. To combat and prevent money laundering crimes, especially those derived from corruption, it is not only necessary to have law enforcement agencies with competent human resources for investigation and prosecution, but it is also essential to build synergy among stakeholders to prevent and combat money laundering crimes. Given that combating money laundering crimes involves multiple institutions such as financial institutions, law enforcement agencies, the Financial Transaction Reports and Analysis Center (PPATK), and other relevant agencies as subsystems, including Bank Indonesia, financial service providers, goods and services providers, the Capital Market Supervisory Agency (BAPEPAM-LK), the Ministry of Communication and Information Technology, the Directorate General of Customs and Excise (DJBC), and law enforcement authorities.